Random telegraphic noise of decananometer transistors - Chng, Joanna Yan Ting (2017)
There has always been an assumption that after voltage-accelerated stressing, the pre-existing or time-zero oxide traps would not be affect. However, this does not seem to hold true in the case of small area MOSFET. This study begins with an introduction to the fundamental understandings of a MOSFET, specifically p-MOSFET. Following which, an understanding of the behaviour of oxide trapped charges. Lastly, to recognise the importance of this study, the author briefly explains on Moore’s law and how in the near future, the trapping and de-trapping of charges would have an increasing impact on the drain current. The study was conducted on a p-MOSFET with channel width 120-nm and channel length 60-nm. Eight sets of data were obtained, with two proving to not add any value to the discussion. Through the study and discussions, the author has shown that, with respect to the device the study was conducted on, the assumption that the after voltage-accelerated stressing, the pre-existing or time-zero oxide traps would not be affect, no longer holds true.